FOREIGN LANGUAGE LEARNING IN IMMERSIVE VIRTUAL ENVIRONMENTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Language learning has always been a challenging but rewarding endeavor. In recent years, advancements in technology have opened up new, exciting possibilities for learning languages. Among these innovations, immersive virtual environments (IVEs) have emerged as a powerful tool in enhancing the process of acquiring foreign languages. These environments offer learners a unique, interactive, and engaging way to practice and acquire linguistic skills, mimicking real-world situations and promoting active participation. This article explores the role of immersive virtual environments in foreign language learning, discussing their benefits, challenges, and real-world applications. It will also provide examples of how various tools and platforms are being used to enhance language acquisition.